If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 9 = 8x + 6 Reorder the terms: 9 + 10x = 8x + 6 Reorder the terms: 9 + 10x = 6 + 8x Solving 9 + 10x = 6 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9 + 10x + -8x = 6 + 8x + -8x Combine like terms: 10x + -8x = 2x 9 + 2x = 6 + 8x + -8x Combine like terms: 8x + -8x = 0 9 + 2x = 6 + 0 9 + 2x = 6 Add '-9' to each side of the equation. 9 + -9 + 2x = 6 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 6 + -9 2x = 6 + -9 Combine like terms: 6 + -9 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5
| y+(y+2)+2(y+2)=58 | | 4s+3t=3 | | -28=3x-5-7+9 | | -28=-5-7+9 | | 3(y-6)=8Y+7 | | 6+10=216 | | 10b-6= | | (3x+4)(7x-14)=0 | | C=8t+35 | | -7x+37=-4x+28 | | 6x-3-(5-x)(2x-1)=0 | | 32=q/2 | | 8x-22=-5(x-6) | | x*15-180=x*6-9 | | 3(v+1)=-2v-32 | | -3t(2t-5)+4t=5t-9 | | 2x(x+1)-(x+1)=0 | | -.02k+1=11 | | 12s=89 | | 6+49x=21x+42 | | 2x+(x+12)=180 | | .02k+1=11 | | 9(x-2)=3(x-2) | | 4.5x-39=2.2x+7 | | n+n+m=2 | | -3t(4t-4)+8t=3t-4 | | 7x+4=x+10 | | x=y/6(16-z) | | -27x^2+48x-5= | | 4(t-3)=2t+7 | | -2(3t-4)+3t=2t-3 | | -27x^3+48x-5= |